Influence of short chain fructo-oligosaccharide (SC-FOS) on the dough rheological, microstructural properties and, bread quality during storage. (15th March 2022) - Sudha, M.L.; Soumya, C.; Saravanan, M.; Madhushree, P.; Singh, Jivjyot; Roy, Saikat; Prabhasankar, P.
Abstract: Objective of this study was to understand the impact of short chain fructo-oligosachharides (SC-FOS) on the dough rheological characteristics and bread quality. SC-FOS was used in place of sucrose and studied for dough rheology, bread making and sensory characteristics. Farinograph, extensograph, amylograph and rheometer were used to evaluate the rheological characteristics. The interaction of SC-FOS with starch was explored from a structural perspective, as well as how SC-FOS influences to keep the bread softer over a period of time. For mechanistic insight, FT-IR (Fourier transform infrared spectroscopy), PXRD (Powder X-ray diffraction), and SEM (Scanning electron microscope) were used to investigate the structural changes. Starch crystallization through molecular and supramolecular reorganization primarily dictates the texture of bakery products, particularly the firmness of product like bread where moisture content is higher; SC-FOS can successfully slow down the crystallization of starch and yield softer product during a shelf life of 7 d. Bread with SC-FOS has shown better retention of water and modulating mobility of water. As a result, incorporating SC-FOS to bread has led to a positive outcome, with improved quality and an excellent sugar replacer. Highlights: SC-FOS influenced the wheat flour dough rheological characteristics. Addition of SC-FOS improved the physical and sensory characteristics of bread. SC-FOS in liquid form influenced to a greater extent. It functioned as a humectant and controlled the mobility of water in bread matrix during storage.